1-[5-(2-Chlorophenyl)-3-(4-methylphenyl)-4,5-dihydro- 1H-pyrazol-1-yl]ethan-1-one - Adam, Farook; Ameram, Nadiah; Samshuddin, Seranthimata; Antony, Moonnanjilikkal Brighten; Ali Khan, Musthakeem (International Union of Crystallography, 2016)
The title compound, C18H17ClN2O, crystallized with two independent molecules (the S and R enantiomers) in the asymmetric unit. The molecules are V-shaped with the two aromatic rings inclined to one another by 78.78 (11) and 81.23 (11)o. In the crystal, molecules are linked via C—. ..O hydrogen bonds, forming chains along the c-axis direction. The chains are linked via C—H...n interactions, forming a three-dimensional framework. The crystal structure was refined as a two-component twin.